PENGARUH K EBIJAKAN MODAL KERJA DAN FAKTOR LAINNYA TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR - AAN MARLINAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
This research aims to obtain empirical evidence about the effect of accounts receivable period, accounts payable period, inventory period, size, age, leverage and asset turnover on profitability. Sample are used in this research are listed as manufacturing company in Indonesia Stock Exchange from 2010 until 2012 using purposive sampling method. Independent-samples t-test and multiple regression analysis are used to test the hypothesis. The results showed that the accounts receivable period of fast have greater profitability than the accounts receivable period of time. In addition, there is no difference in profitability between accounts payable and inventory period of time and fast. While the size, firm age and asset turnover positive effect on profitability. While leverage negatively affect profitability.